Investigation on the Compressive Strength of Gunny Sack Fiber Concrete under High-Temperatures - Nur Fithriani F. Cholida; Purwanto P.; Hani Purwanti (Universitas Islam Sultan Agung, 2020)
Gunny sack fiber concrete has not been explored especially the behavior under high temperatures. This paper presents the results of an experimental investigation of gunny sack fibrous concrete (percentage of 0.5% of volume) given a monotonic- compressive load. A number of cylindrical test specimens were made which consisted of control specimens and which were incinerated at temperatures of 300oC, 600oC and 900oC. The concrete -compressive strength was designed with three variations of the cement water ratio to get the compressive strength of a standard cylinder with normal, medium and high -quality compressive strength categories. Experimental results show that normal to high quality concrete can be produced with gunny sack fiber substitution. The compressive strength of the gunny sack fiber concrete decreased significantly from the control specimen to the specimen which was burned at 300oC. The loss of compressive strength from the control specimens to the post-burn specimens of medium quality and high -quality of gunny sack fiber concrete was the same compared with the loss of compressive strength of normal- quality concrete. This study also carried out a comparison of the degradation of the compressive strength of steel fibrous concrete with gunny sack fiber in post-burn conditions.